The establishment of sustainable food farmland area in District of Aceh Besar - Muhammad Yasar; Chamhuri Siwar (Syiah Kuala University, 2012)
Conversion activity of paddy land to non-agricultural use of the growing opportunity to threaten national food security. One anticipation step is to set the sustainable food farming land (LPPB). This study aims to provide information about the food farming land that should be protected from the threat of conversion in the district of Aceh Besar. The approach taken is through the classification of land based on biophysicalpotency. Data obtained through survey, observation, secondary data collection, and literature studies. The study results indicate that there are four categories of paddy land, namely: the main land I (9 districts), the main land II (7 districts), the secondary land I (5 districts), and secondary land II (2 districts). The main land is the land which is suggested to be an everlasting land (sustainable) for reliable biophysical characteristics, while the secondary land could be converted as long as it is based on the main reason and more urgent.